Communicate or die: a model for HPV+ and HPV− CSCs and their interactions with SDF-1α - Jungbauer, Frederic; Aderhold, Marc Christoph; Birk, Richard; Hörmann, Karl; Kramer, Benedikt; Walter, Beatrice; Thorn, Carsten Volker; Lammert, Anne (Anticancer research, 2017)
Background/Aim: Cancer stem cells (CSCs) are suspected of being a reason for limited therapy in head and neck squamous cell carcinoma (HNSCC). Stromal cell-derived factor-1 alpha (SDF-1 alpha) plays a critical role in the communication between CSCs and their microenvironment. We investigated the influence of SDF-1 alpha on HPV+/HPV-SCC cell lines to find an approach of explanation for the superior prognosis of HPV+ HNSCCs. Materials and Methods: We evaluated the expression of CD44/CXCR4 on HPV+/HPV- SCC cell lines and monitored the influence of SDF-1 alpha on proliferation, morphology and migration of HPV+/HPV- SCCs. Results: HPV- SCCs showed a significant increase of podia formation and an intensified migration towards SDF-1 alpha. HPV+ SCCs rested nearly unaffected by SDF-1 alpha. Conclusion: Weakened reaction to SDF-1 alpha in HPV+ SCC could lead to an impaired communication between CSCs and their niche, that would result in an increased exposure of CSCs to the harming influence of e.g. chemotherapeutic agents.